Strategic drought risk management: eight 'golden rules' to guide a sound approach. Issue 2 (3rd April 2017) - Sayers, Paul B; Yuanyuan, Li; Moncrieff, Catherine; Jianqiang, Li; Tickner, David; Gang, Lei; Speed, Robert
ABSTRACT: Major droughts are an ever-present threat in almost all countries; a threat that is set to increase in response to climate change and the influence of socio-economic change on the demand for, and use of, water. Historically droughts have been responded to 'as they happen' leading to incremental shifts in approach as lessons are learnt. Given the significance of the challenge now faced in this heuristic approach is no longer fit for purpose and a new approach is required. Based upon a combination of expert workshops, detailed international case studies and analysis of past droughts, this paper sets out a strategic approach to managing water resources that specifically addresses drought. The framework encourages a focus on long-term outcomes (for people, ecosystems and economies) and views drought as a water-related risk, not simply a hazard. Strategic drought risk management (SDRM) is presented as a multi-scale endeavour, providing both local and regional solutions whilst addressing short- and long-term challenges. It seeks to implement a diverse portfolio of measures during non-drought conditions as well in the run-up to, during and after a drought event whilst recognizing the critical interdependences between human systems and freshwater ecosystems. The paper concludes by presenting eight 'Golden Rules' to guide a sound approach to SDRM.